Blessings the Tsoknyi Nangchen nuns of Tibet - Hitchcock, Victress; Gere, Richard 1949-; Tshogs-gnyis-rin-po-che 1966- (Pundarika Foundation, 2010)
"The purpose of this feature-length documentary is to expand awareness of the Nangchen Nuns, to explore the roots of their wisdom and compassion and to show how we, as ordinary human beings seeking happiness in a modern world, can find that same thread of sanity and inner strength in the everyday confusion of our lives"--Http://www.pundarika.org